2008
DOI: 10.1016/j.jallcom.2007.08.085
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic and kinetic studies of Mg–Fe–H after mechanical milling followed by sintering

Abstract: The transition metal complex hydride Mg 2 FeH 6 has been successfully synthesized utilizing mechanical milling of a 2Mg-Fe mixture followed by heating at 673 K under 6 MPa of hydrogen pressure, without pressing step. The obtained yield of Mg 2 FeH 6 was about 50%. Hydrogen storage properties of the Mg-Fe-H system, i.e. capacities, absorption/desorption kinetics and thermodynamic parameters, were examined. The pressurecomposition isotherm (PCI) measurements of the samples at 548-673 K showed that the alloys pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 21 publications
(101 reference statements)
5
49
0
Order By: Relevance
“…[20,21]; line (b) represents the equilibrium pressure of the dehydrogenation of Mg2FeH6, according to Refs. [22][23][24].…”
Section: Optimal Composition Ratio For the Stoichiometric Reaction Bementioning
confidence: 99%
“…[20,21]; line (b) represents the equilibrium pressure of the dehydrogenation of Mg2FeH6, according to Refs. [22][23][24].…”
Section: Optimal Composition Ratio For the Stoichiometric Reaction Bementioning
confidence: 99%
“…It is important to emphasize that the complex hydride Mg 2 FeH 6 has a lower equilibrium pressure than β-MgH 2 [2,4,8] . This means that Mg 2 FeH 6 is a more stable hydride than β-MgH 2 .…”
Section: Kinetics Of Hydrogen Absorptionmentioning
confidence: 99%
“…Some authors suggested that Mg 2 FeH 6 is formed directly from the reaction of 2Mg+Fe+3H 2 [1,2,6,8] , while others reported that the reaction involves two steps: the first one is the formation of MgH 2 , and secondly, the reaction of magnesium hydride with Fe [5,[9][10][11] . Polanski et al 11 using in-situ synchrotron X-ray diffraction showed that MgH 2 is the Mg 2 FeH 6 precursor.…”
Section: Introductionmentioning
confidence: 99%
“…Puszkiel et al [48] synthesized Mg-Fe-H composites by mechanical milling followed by sintering at 400°C at 6 MPa of hydrogen pressure. The yield of obtained Mg 2 FeH 6 was about 50%.…”
Section: Nanodispersionmentioning
confidence: 99%